2018
DOI: 10.1093/cid/ciy190
|View full text |Cite
|
Sign up to set email alerts
|

Case Fatality Rate of Enteric Fever in Endemic Countries: A Systematic Review and Meta-analysis

Abstract: We conducted a systematic literature review and meta-analysis and estimated the case fatality rate of enteric fever to be 2.49% (95% confidence interval, 1.65%–3.75%; n = 44), 2.5 times higher than what was assumed up until now.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Furthermore, typhoid incidence varies over both space and time. The probability for hospital admission and case fatality are also very heterogeneous 19 and are difficult to assess without confirming cases through laboratory culture. Because precise incidence, hospital admission, and mortality rate estimates are difficult to obtain, we identified the minimum values at which TCV vaccination becomes optimal compared with no vaccination in each country, which could be helpful in identifying priority regions to target for vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, typhoid incidence varies over both space and time. The probability for hospital admission and case fatality are also very heterogeneous 19 and are difficult to assess without confirming cases through laboratory culture. Because precise incidence, hospital admission, and mortality rate estimates are difficult to obtain, we identified the minimum values at which TCV vaccination becomes optimal compared with no vaccination in each country, which could be helpful in identifying priority regions to target for vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of country-specific vaccine coverage were based on Gavi's demand forecast (appendix pp 18–20). We identified country-specific data on case-fatality rates (eight countries), 19 hospital admission rates (four countries), 20 and costs of vaccine delivery for routine (four countries) and campaign doses (13 countries) 26, 27, 28. For countries without such data, we did random-effects meta-analyses, using all these available studies to inform common estimates (appendix p 22).…”
Section: Methodsmentioning
confidence: 99%
“…The hospitalization and case fatality rates are particularly influential when estimating the cost-effectiveness of typhoid vaccination strategies [31–33]. However, studies have found considerable heterogeneity in the hospitalization and case fatality rates of typhoid fever cases in different parts of the world [34, 35]. In particular, estimates of the case fatality rate that are derived only from blood culture–confirmed patients may overestimate the mortality rate, as these cases could represent the more severe end of the spectrum of illness.…”
Section: Predicting Typhoid Burden and Vaccine Impactmentioning
confidence: 99%
“…Untreated, case fatality ratios range from 2.49% in enteric fever,75 0-39.7% in icteric leptospirosis,76 and 0-33% in scrub typhus 77…”
Section: What Are the Possible Complications?mentioning
confidence: 99%